Pemberian Lilin Aromaterapi Melati Terhadap Penurunan Kecemasan Pada Ibu Nifas - Pricillia Agustina Yudi; Norif Didik Nur Imanah; Dahlia Arief Rantauni; Septi Tri Aksari (STIKes Ibnu Sina Ajibarang, 2024)
Changes that occur during the postpartum period, both physiologically and psychologically, are often experienced by mothers, namely fatigue, changes in roles, and anxiety. One of the factors that causes anxiety in postpartum mothers is trauma caused during childbirth which causes anxiety. Handling anxiety in postpartum mothers can be done non-pharmacologically, namely with jasmine aromatherapy candles. This research aims to determine how giving jasmine aromatherapy candles reduces anxiety in postpartum mothers using qualitative research with case studies and data sources and types of data using interviews, examinations and observations. The implementation technique was carried out by Mrs. L by giving jasmine aromatherapy candles for approximately 10-15 minutes a day and giving aromatherapy to Mrs. L 6 times. The use of aromatherapy candles recommended to Mrs. L is done at night by placing an aromatherapy candle next to the bed so that the postpartum mother can inhale it. Giving jasmine aromatherapy candles to Mrs. L for 6 days, the results showed that Mrs. L felt more relaxed than before he was given the jasmine aromatherapy candle, as indicated by the mother feeling less anxious about caring for her baby and being mildly anxious, so giving the jasmine aromatherapy candle had an impact on reducing Mrs. L's anxiety. L.